Protein engineering in industrial biotechnology - Alberghina, Lilia (Harwood Academic, 2014)
Protein engineering has proved to be one of the more fruitful technological approaches in biotechnology, being both very powerful and able to generate valuable intellectual property. This volume aims to present examples in which the application of protein engineering has successfully solved problems arising in industrial biotechnology.